Metacognition and foreign language reading: fostering awareness of linguistic form and cognitive process in the teaching of ianguage through text - Braga, Denise B.; Busnardo, Joanne (Lenguas Modernas, 2017)
The result ofour teaching practice in Brazil during the 1980’s led us to perceive the risk of not taking into consideration the peculiarities of the local context in the application of imported teaching methodologies. Contrary to what "natural approaches" predict, the teaching of Reading of a foreign language in a nonimmersion situation demands some kind of teacher intervention. The present paper aims to reflect on the notion of metacognition as a path for intervention and suggess that written material has great potential for fostering language awareness and learning within our particular situation.